A model of cylindrical inhomogeneity with spring layer interphase and its application to analysis of short-fiber composites. (15th January 2017) - Nazarenko, Lidiia; Stolarski, Henryk; Altenbach, Holm
Highlights: Model based on a statistical method and the concept of energy-equivalent inhomogeneity. The interface effects introduced via spring layer model. Real inhomogeneity and its interphase replaced by energy-equivalent one. Modified properties of equivalent inhomogeneity incorporate the interphase effects. Transversely isotropic short-fiber composites are analyzed. Abstract: A model for randomly distributed, unidirectional, short-fiber composites with the spring layer model of interphases is presented and evaluated by means of numerical examples. It combines the notion of the energy-equivalent inhomogeneity and the method of conditional moments, proposed to evaluate the effective properties of random composites. The model leads to closed-form solution for effective properties of the composite. Given that the results for short-fiber composites with interphases do not appear to exist in the literature, the verification of the proposed methodology was possible through comparisons with the solutions for composites with infinite fibers. The limit values of the results developed here for short fibers are in an excellent agreement with those available in the literature for infinite fibers.